Evaluation of wound healing properties of bioactive aqueous fraction from Moringa oleifera Lam on experimentally induced diabetic animal model - Muhammad AA; Arulselvan P; Cheah PS; Abas F; Fakurazi S (Dove Medical Press, 2016)
Abubakar Amali Muhammad,1 Palanisamy Arulselvan,1 Cheah Pike See,2 Farida Abas,3 Sharida Fakurazi1,2 1Laboratory of Vaccine and Immunotherapeutics, Institute of Bioscience, 2Unit of Anatomy, Department of Human Anatomy, Faculty of Medicine and Health Sciences, 3Department of Food Science, Faculty of Food Science and Technology, Universiti Putra Malaysia, Serdang, Malaysia Abstract: Diabetic foot ulcer is a serious complication of diabetes, which affects a significant percentage (15%) of diabetics and up to 15%–24% of those affected may require amputation. Therefore, the economic burden of diabetic foot ulcers is enormous and is associated with high cost of treatment and prolongs hospitalization. The present study was conducted to evaluate antibacterial and in vivo wound healing activities of an aqueous fraction of Moringa oleifera on a diabetic condition. Antibacterial activity testing was carried out using agar well and tube dilution techniques. The in vivo study was conducted using six groups of animals that comprise of one normal and diabetic control group each, three treatment groups of 0.5%, 1%, and 2% w/w aqueous fraction, and a positive control group (1% w/w silver sulfadiazine). Rats were induced with diabetes using a combination of streptozotocin 65 and 150 mg/kg nicotinamide daily for 2 days, and excision wounds were created and treated with various doses (0.5%, 1%, and 2% w/w aqueous fraction) daily for 21 days. Biophysical, histological, and biochemical parameters were investigated. The results of the study revealed that aqueous fraction possessed antibacterial activity through inhibition of growth of Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli organisms. The topical application of aqueous fraction revealed enhancement of wound healing under sustained hyperglycemic condition for the duration of the experiment. This enhancement was achieved through decreased wound size, improved wound contraction, and tissue regeneration, as well as downregulation of inflammatory mediators, such as tumor necrosis factor-α, interleukin-1β, interleukin-6, inducible nitric oxide synthase, and cyclooxygenase-2, and upregulation of an angiogenic marker vascular endothelial growth factor in wound tissue treated with various doses of aqueous fraction of M. oleifera. The findings suggest that aqueous fraction of M. oleifera containing Vicenin-2 active compound may accelerate wound healing in hyperglycemic condition. Keywords: aqueous fraction, Vicenin-2, wound healing, inflammatory mediators